Physician Performance Measurement Barriers in Private General Hospitals Around Medan City - Lubis, Arfah Mardiana; Nasution, Puteri Citra Cinta Asyura (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
Study results from early 2016 across 20 private general hospitals around Medan city, show there are 10 hospitals that have a physician performance measurement. However, the Medical Committee perceived some unknown barriers on measurement of physician performance. Should it be known, the hospitals can improve and enhance physician performance measurement effectively and efficiently. Therefore, this study aims to uncover the barriers on physician performance measurement in Private General Hospitals around Medan city. From the interviews with 10 Medical Committees and 6 document studies in 10 Private General Hospitals around Medan city which have a physician performance measurement, we found that the barriers on physician performance measurement are: unsupportive human resources, improper Medical Committee monitoring, unwillingness of physicians to be assessed, and assessors tendency toward giving moderate and good score. Therefore, we recommended that Medical Committee in each Private General Hospital around Medan or supervisors who will assess the performance of the physicians to attend performance measurement training to minimize biases and errors in filling out the sheet of physician performance measurement. Training should also be followed by an explanation that physicians should treat this performance measurement as a positive thing, because it can help the medical profession improve its professionalism.